2014
DOI: 10.1001/jamaoto.2014.1
|View full text |Cite
|
Sign up to set email alerts
|

Current Thyroid Cancer Trends in the United States

Abstract: There is an ongoing epidemic of thyroid cancer in the United States. The epidemiology of the increased incidence, however, suggests that it is not an epidemic of disease but rather an epidemic of diagnosis. The problem is particularly acute for women, who have lower autopsy prevalence of thyroid cancer than men but higher cancer detection rates by a 3:1 ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
1,223
3
35

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,451 publications
(1,290 citation statements)
references
References 26 publications
(25 reference statements)
29
1,223
3
35
Order By: Relevance
“…During this period, the incidence rate of thyroid cancer was 13. 7 per 100,000 p-y-almost double the incidence rate of 7.1 for1990-1999 and similar to the incidence of 14.3 observed in 2009 by the SEER analysis (1). The analysis including the mechanism of detection revealed that the rapid increase in incidence of TC during the last period, 2000-2012, is attributable to the increased diagnosis of occult TCs, whereas the incidence of clinically recognized TC has not changed over the last four decades.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…During this period, the incidence rate of thyroid cancer was 13. 7 per 100,000 p-y-almost double the incidence rate of 7.1 for1990-1999 and similar to the incidence of 14.3 observed in 2009 by the SEER analysis (1). The analysis including the mechanism of detection revealed that the rapid increase in incidence of TC during the last period, 2000-2012, is attributable to the increased diagnosis of occult TCs, whereas the incidence of clinically recognized TC has not changed over the last four decades.…”
Section: Discussionsupporting
confidence: 80%
“…The Surveillance, Epidemiology, and End Results (SEER) program data suggests that the incidence of TC increased from 4.9 in 1975, to 14.3 cases per 100,000 individuals in 2009 (1). Currently, TC has the most rapid increase in incidence of any cancer, such that it has been estimated that by 2019 TC will become the third most common cancer in women (2).…”
mentioning
confidence: 99%
“…[1][2][3][4] The prognosis of localised thyroid cancer is excellent. However, age, sex, tumour size, extrathyroidal extension, histological grade and type, local invasion, multicentricity, presence of metastatic disease, and completeness of surgical resection are known to be independent predictors of survival in thyroid malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this huge pool of subclinical cases, the prevalence of thyroid cancer in the United States is only 0.5 million patients (2), indicating that <3% of this subclinical reservoir has been detected and diagnosed. Unless the aggressive evaluation of subcentimeter thyroid nodules with high-resolution ultrasound (US) and US-guided fine-needle aspiration (FNA) is curtailed, the incidence of thyroid cancer will continue to increase dramatically as more and more cases of subclinical, low-risk papillary thyroid cancer (PTC) are identified (3,4).…”
mentioning
confidence: 99%